Summary of FDA Workshop on Ischemia Reperfusion Injury in Kidney Transplantation. Issue 5 (8th April 2013) - Cavaillé‐Coll, M.; Bala, S.; Velidedeoglu, E.; Hernandez, A.; Archdeacon, P.; Gonzalez, G.; Neuland, C.; Meyer, J.; Albrecht, R.
Abstract The Food and Drug Administration (FDA) held an open public workshop in September 2011 to discuss the current state of science related to the effects of ischemia reperfusion injury (IRI) on outcomes in kidney transplantation. Topics included the development of IRI and delayed graft function (DGF), histology and biomarkers, donor factors, recipient factors, organ quality and organ preservation by means of cold storage solutions or machine perfusion. Various mechanisms of injury and maladaptive response to IRI were discussed as potential targets of intervention. Animal models evaluating specific pathophysiological pathways were presented, as were the limitations of extrapolating animal results to humans. Clinical trials of various drug products administered in the peri‐transplant period were summarized; a few demonstrated early improvements in DGF, but none demonstrated an improvement in late graft function. Clinical trial design for IRI and DGF were also discussed.